An Automated Perifusion System for Modifying Cell Culture Conditions over Time. Issue 1 (December 2016) - Whitticar, Nicholas; Strahler, Elisha; Rajan, Parthiban; Kaya, Savas; Nunemaker, Craig
Abstract Background Cells are continuously exposed to changes in their environment. Endocrine systems, in particular, communicate by rhythms and feedback loops. In this study, we developed an automated system to produce such conditions for cultured cells in a precisely timed manner. We utilized a programmable pair of syringe pumps for inflow and a peristaltic pump for outflow to create rhythmic pulses at 5-min intervals in solutions that mimic the endogenous patterns of insulin produced by pancreatic islets as a test case. Results This perifusion system was first tested by measuring trypan blue absorbance, which was intermittently added and washed out at 3:3 and 2:3 min (in:out). Absorbance corresponded with patterns of trypan blue delivery. We then created patterns of forced oscillations in islets by intermittently switching between solutions containing 28 millimolar (mM) glucose (producing high levels of intracellular calcium ([Ca2+ ]i ) and insulin secretion) and 28 mM glucose + calcium-channel blocker nifedipine (producing low levels of [Ca2+ ]i and insulin secretion). Forced perifusion effects were monitored by fura-2 AM fluorescence measurements of [Ca2+ ]i . Islets showed uniform oscillations in [Ca2+ ]i at time intervals consistent with the perifusion pattern, mimicking endogenous pulsatility. Conclusions This study highlights a valuable method to modify the environment of the cell culture over a period of hours to days.